TRANSFORMATIONAL LEADERSHIP OF THE PRINCIPAL IN THE IMPLEMENTATION OF THE PROFESSIONAL LEARNING COMMUNITY (PLC) - Lagarense, Fabiola; Purwanto, Nurtanio Agus; Hemamalini, Hemamalini (JURNAL EDUSCIENCE, 2025)
Purpose - This research aims to determine and describe the transformational leadership of school principals in implementation Professional Learning Community (PLC) at the Elementary School level.Methodology - The method used in this research is descriptive qualitative. This research was conducted at SD Negeri Kyai Mojo and SD Negeri Vidya Qasana. The subjects of this research are school principals and teachers. Data collection techniques use observation, interviews and document study. Data were analyzed by referring to Miles & Huberman's theory, namely data collection, data condensation, data presentation, and drawing conclusions.Findings - The results in this study show that: (1) Planning Professional Learning Community (PLC) at SD Negeri Kyai Mojo, namely: formulating a clear vision and goals, carrying out needs analysis, organizing strategic resources (forming a learning community team "Ngudi Kawruh" and budgeting it in the RKAS), preparing a learning community schedule, building effective communication with stakeholders. Meanwhile planning Professional Learning Community (PLC) at SD Negeri Vidya Qasana, namely: integrating the vision and goals of the learning community with the school's vision and the Independent Curriculum, managing the learning community's schedule, providing external and internal school resource persons, and managing the budget. (2) Implementation Professional Learning Community (PLC), among others; determining material, determining resource persons in the learning community or involving external resource persons, continuous reflection and evaluation, collaboration and professional development of teachers in sharing knowledge and good practices, learning communities are held every Friday of every week. (3) Obstacles faced include; limited time, budget, and teacher commitment. The solutions implemented by the principal include; optimizing internal resources, managing learning community schedule adjustments, and implementing a collaborative approach that supports each other.Significance – The results of the research can provide practical insight for school principals and stakeholders in developing a collaborative culture that supports teacher professional development and can be a consideration for other schools in enriching their understanding of the principal's transformational leadership role in designing, implementing and overcoming obstacles in the Professional Learning Community (PLC).